42 Systemic Estradiol Menopause Management: Return to the Old-Fashioned Way. Issue 1 (1st April 2022) - Goldstein, S; Yee, A; Goldstein, I
ABSTRACT: Introduction: Low systemic estradiol values (<10 pg/ml) experienced by menopausal women are associated with multiple symptoms including hot flashes, night sweats, insomnia, mood changes/irritability, vaginal dryness, dyspareunia, dysuria, low libido, reduced arousal/orgasm, cognitive changes, weight gain and slowed metabolism. Intramuscular estradiol cypionate was first described for medical use in 1952 to treat symptoms of menopausal ovarian failure. Systemic management has evolved, including daily gels, weekly/twice weekly patches and three-month vaginal rings. These therapies have successfully reduced bothersome symptoms in >60% women presenting to our clinic. A subset of women cannot achieve sufficient symptom relief using these strategies due to lack of efficacy, negative side effects, (rings cannot stay in the vagina; values are too high initially and then too low; patches cause rashes or fall off; gels are too messy) or financial concerns. For these patients, we have advised returning to the "old-fashioned way" using weekly or twice weekly intramuscular (IM) injection of either estradiol valerate or cypionate. Objective: This study examines experiences of this subset of women in our practice using injections of estradiol valerate or cypionate for either enhancing efficacy or financial reasons. Methods: This chart review identified 22 patients (mean age 61 +/- 8 years) who had been prescribed estradiol valerate or cypionate when symptoms of genitourinary syndrome of menopause (GSM) persisted despite use of estradiol replacement gels/patches/rings, or cost was prohibitive. We have advised weekly/twice weekly IM injection of either estradiol valerate (20 mg/ml; starting dose 0.05 ml (1 mg) weekly or 0.025 ml (0.5 mg) twice weekly) or estradiol cypionate (5 mg/ml; starting dose 0.2 ml weekly (1 mg) or 0.1 ml (0.5 mg twice weekly), utlizing 1 ml syringes with 27-gauge ½ inch needle. Injections were administered into the vastus lateralis on the antero-lateral surface at mid-thigh. Alcohol was used to prepare the skin, and compression was applied for 2 minutes after the injection. We compared relief of bothersome symptoms from earlier estradiol treatments to current IM injection and monthly costs of each treatment based on GoodRx prices, assuming medications were not covered by insurance. Results: All patients using injections of estradiol valerate or cypionate had their estradiol-based GSM symptoms ameliorated without complaint of inconvenience or discomfort using injections. All described injection pain as minimal. No significant side effects were noted with IM injection. The risks of IM injections of estradiol are similar to those of topical administration, requiring concomitant progesterone use in women with a uterus. Concerning finances, using a GoodRx coupon, a 5 ml bottle of estradiol valerate lasting at least a year costs approximately 50, reducing monthly cost to approximately 5/month. A 5 ml bottle of estradiol cypionate lasting at least 6 months costs approximately 150, thus about 25/month. In contrast, generic patches can cost approximately 40/month, gels 150/month and the ring 170/month. Conclusions: While there remains an aversion to injections in some patients, the motivation for IM systemic estradiol replacement superseded any inconvenience. For certain individuals, the "old-fashioned way" works better both in terms of efficacy and cost, providing relief of bothersome GSM symptoms. Disclosure: No